The process of education - Bruner, Jerome S. (Jerome Seymour) (A Harvard paperback., 1977)
In this classic argument for curriculum reform in early education, Jerome Bruner shows that the basic concepts of science and the humanities can be grasped intuitively at a very early age. He argues persuasively that curricula should he designed to foster such early intuitions and then build on them in increasingly formal and abstract ways as education progresses. Bruner's foundational case for the spiral curriculum has influenced a generation of educators and will continue to be a source of insight into the goals and methods of the educational process.